Acute mountain sickness: acute lung edema - Lizárraga Morla, Leoncio (1955)
The climatic aggression altitude well known in Inca times, whose law surprised by the deep knowledge of the phenomena "meteoropatológicos cosmo" has created a variety of climatic or physiological human race (Monge), which means it offers different biological characteristics the man at sea level.